The Effect of PALAR-Assisted MID on Students' Mathematical Communication Ability and Self Confidence - Zalmira Aidina Barus; Tanti Jumaisyaroh Siregar (Universitas Negeri Makassar, 2022)
This study aims to determine the effect of the Meaningful Instructional Design learning model assisted by PALAR Media on students' mathematical communication skills and self-confidence. The method used by the researcher is a quantitative research method, with a quasi-experimental research model with a Pretest-Posttest Control Group Design research design. The data collection technique used is a test of mathematical communication skill sand a self-confidence questionnaire. Data analysis techniques used are normality test, homogeneity, and t-test. The results of theresearch are: (1) there is an effect of the PALAR media-assisted Meaningful Instructional Design learning model on students' mathematica lcommunication skills; (2) there is an influence of the PALAR media-assisted Meaningful Instructional Design learning model on students' self-confidence.